Evaluation of Inhaler Technique in Patients with Asthma and Chronic Obstructive Pulmonary Disease in Andaman and Nicobar Islands – An Observational Study - M. Natraj; Vishal Singh; T. Anbarasan (Journal of Association of Pulmonologist of Tamil Nadu)
Objective: Both asthma and chronic obstructive pulmonary disease (COPD) cause significant morbidity and mortality worldwide. The mainstay treatment for both diseases includes inhalational therapy. A high percentage of patients have symptoms that are not well controlled in spite of using effective medications. One potential reason could be poor inhaler techniques. This results in poor control of the disease along with repeated exacerbations and hospital admissions. Materials and Methods: This was an observational study done at the Department of Respiratory Medicine, Andaman and Nicobar Islands Institute of Medical Sciences, Port Blair, Andaman and Nicobar Islands. We enrolled a total of 100 patients who presented to our department during the study period of January 2024 to June 2024. A detailed history was recorded that included questions such as age, sex, disease for which inhalers were prescribed, and the type of inhalers they were using metered dose inhaler (MDI, MDI with spacer, and dry powder inhaler [DPI]). We requested the patients to demonstrate the inhaler technique in the presence of the healthcare professional which was subsequently assessed using a standard validated checklist. Results: The majority of the patients were in the age group of 51–70 years of age (55%) with 46% of them being male patients. Fifty-five percent of the patients were diagnosed with COPD while 45% had asthma. Fifty-two percent of the patients were using MDI, 36% were using MDI with space while the remaining 12% of the patients were using DPI. Ninety percent of the patients had a faulty technique. Conclusion: The majority of the patients had a faulty technique leading to poor control of the disease. Patients who are using inhaler medications should have their inhaler techniques checked frequently to obtain proper control of their disease.